Underlying risk preferences and analyst risk‐taking behavior. (9th March 2020) - Cleary, Sean; Jona, Jonathan; Lee, Gladys; Shemesh, Joshua
Abstract: We investigate the relationship between underlying risk preferences on analysts' work‐related decisions. Specifically, we examine whether facial width‐to‐height ratio (fWHR), an innate personal characteristic that has been linked to financial risk tolerance, is associated with analysts' stock coverage decisions and the boldness of their earnings forecasts and stock recommendations. We find that high‐fWHR analysts cover firms with lower earnings predictability, and issue bolder forecasts and recommendations. Our findings shed new light on the black box of analyst decision making, assisting investment practitioners in evaluating the information content produced by different types of analysts and understanding the observed dispersion in analyst forecasts.